KAJIAN PRODUKTIVITAS DAN EFISIENSI PEMANFAATAN LAHAN SISTEM PERTANIAN TERPADU PADA AGROEKOSISTEM LAHAN KERING DATARAN RENDAH DESA FATUKANUTU KABUPATEN KUPANG - Maria Klara Salli; Rupa Matheus; Mika S. Rampoon (Politeknik Pertanian Negeri Kupang, 2018)
Research about land productivity and efficiency of integrated farming systems on dryland agroecosystems had been conducted in farmers owned land in Fatukanutu village with land characteristics at a slope of <15% and altitude <500 m above the sea level. This research is secondyear research, which was carried out from January to November 2018. The purposes of this study are to implement an integrated farming system in dryland and lowland agroecosystems, to assess land productivity in an integrated agricultural system model (SPT) and the efficiency of land use on cropping patterns in the SPT model in lowland and dryland agroecosystems. The results showed that the model applied in the field is a banana-based integrated farming system, which is following the local and potential components such as livestock, food crops (maize), vegetables and fodder ( lamtoro) with intercropping harvesting system (Tumpangsari and TumpangGilir). Compared to monoculture crops, land productivity in integrated farming systems in dryland banana zone in agroecosystems ismore productive. Also, cropping patterns in SPT model are beneficial because the LER value is > 1, there is efficiency in land use on banana-based SPT, with the LER value of banana-corn 1.15, banana-vegetable 1.65 and banana-maize-vegetable 2.80